(untitled) (Altre Modernità, 2011)
The son is configured into the orbit of Cuban popular music as the mulatto music genre par excellence, thanks to the amalgam of musical elements and structural features of Spanish and African origins. In its heyday - when are defined new modes of interpretation and new sonic possibilities - shares political and cultural unrest of vanguards that, through the recognition of the African component, try to build a coherent concept of nation, highlighting the contribution of black people to cultural and political processes. This work is based on the hypotheses suggested in some cuban studies recently published, about the causal relationship between the son’s development and the shape of national identity in the period of the Wars of Independence, to come to find through the thematic analysis of representative texts the genre’s functioning within this perspective.